Unique Culinary Success in Medan City as a Tourism Destination - Elfitra Desy Surya (International Journal of Management, Economic and Accounting, 2023)
This essay analyzes and discusses the relationship between distinctive local cuisine and destination branding, utilizing consumer satisfaction as a mediating factor. Design, methodology, and approach: A nonprobability sampling technique combined with the judgemental sampling method was employed for the research sampling. One hundred forty tourists who had twice recently visited Medan City participated in the survey. The data were analyzed using SMART PLS and path analysis. Research findings: The Results revealed that while customer satisfaction greatly impacted branding destination, Unique Local Food considerably impacted customer joy. Likewise, exceptional regional cuisine significantly impacts destination branding by making tourists happy. The empirical results of this study offer strong support for the proposed Path analysis, which aims to take distinctive local food, customer satisfaction, and branding destinations into account simultaneously. Even though previous studies have not thoroughly explained the connection between factors, this is still the case. Practitioners/Policy Implications: The study suggests that Medan can effectively promote and advertise its image and cultural tourism performance since travelers know it as a city with a distinct culinary scene, leaving solid impressions. According to a study, Medan visitors do not form emotional bonds over the cuisine. Research Limitations/Implications: The researchers encountered challenges when collecting data for this study because most visitors were local tourists. Few domestic and international tourists were present simultaneously, making it difficult to distribute the questionnaire evenly.